Insight into the kinetically and thermodynamically controlled biosynthesis of silver nanoparticles. Issue 9 (4th November 2020) - Anand, Shreya; Pandiyan Kuppusamy, Raghu Raja; Padmanabhan, Padmini
Abstract : The mechanism of nanoparticles (NPs) synthesis is a crucial prerequisite for the engineering of desirable material properties and is elusive due to the difficulty of studying the synthesis path and also due to lack of published work. The present study moves beyond the current conventional study of characterisation of NPs synthesis. It focuses on study of classical kinetics of metal NP using silver as a model metal to perform the required experiments, it aimed at understanding the crystallisation process which is the major root for the synthesis of metal NP. The authors have chosen biological approach to explain the process of synthesis of metal NP using inductively coupled plasma – optical emission spectroscopy that directly analyses the concentration of metal NPs. Alpha‐amylase solution, when incubated with silver nitrate solution, turned brown at a specific concentration of enzyme and substrate, which shows the formation of silver NPs. Inductively coupled plasma data and dynamic light scattering spectra were studied to understand the kinetics and the kinetics model was obtained. The enthalpy (Δ H *), activation energy (Δ E *), and equilibrium constant ( K ) were calculated for understanding the thermodynamics of the reaction. The process of NP synthesis is dependent on the kinetics of the reaction, and other process parameters limit the thermodynamics of the process.